Recovery From Ostracism Distress: The Role of Attribution - Yaakobi, Erez (Frontiers in Psychology, 2022)
Ostracism is known to cause psychological distress. Thus, defining the factors that can lead to recovery or diminish these negative effects is crucial. Three experiments examined whether suggesting the possible causes of ostracism to victims could decrease or eliminate their ostracism distress. They also examined whether death-anxiety mediated the association between the suggested possible cause for being ostracized and recovery. Participants (N = 656) were randomly assigned to six experimental and control groups and were either ostracized or included in a game of Cyberball. Two control conditions were used: participants who were ostracized but received no explanation, and participants who were included. Immediately after the ostracism experience, participants in the experimental groups were presented with one of four causes for being ostracized, using locus of control (internal, external) and stability (stable, unstable), the two causal dimensions of Weiner’s attribution theory. After a short delay they were administered a mood or needs-satisfaction questionnaire. The results highlight the interaction between locus of control and stability, and underscore the relative importance of different attributions in alleviating self-reported ostracism distress. Specifically, both external and unstable attributions decreased distress, and an unstable attribution led to complete recovery in some participants. Thus, recovery from ostracism may be accelerated when the victim receives an explanation for ostracism that attributes the incident to unstable, external causes soon after the incident. Death-anxiety fully mediated the association between locus of control attribution and mood, but for on needs-satisfaction or the stability of the attribution.